Effects of the learning tasks and the leadership profile of the coach on the perception of decision-making in young - de Albuquerque, L. R.; Scheeren, E.; Vagetti, G.; Oliveira, V. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The objective of the research was to investigate the effects of the learning tasks and leadership profile of the coach on the subjective perception of decision-making. In total, 910 Brazilian adolescents (14.00 ± 1.8 years) and 57 Brazilian coaches (45.57 ± 7.25 years) were included in the study, participants of a sports program in 37 public schools in the city of Curitiba in the state of Paraná. Ordinal logistic regression was used to verify the independent associations between the variables and the tertiles of the scores for each decision-making characteristic. The small-sized game learning tasks were positively associated with commitment to decision-making learning (CR = 1.21, 95% CI = 1.01-1.49). Positive associations were also found between the coaches' leadership profile and decision-making competence.